2018
DOI: 10.5194/acp-18-12581-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gaseous criteria pollutants in the Bangkok Metropolitan Region, Thailand

Abstract: Abstract. The analysis of gaseous criteria pollutants in the Bangkok Metropolitan Region (BMR), Thailand, from 2010 to 2014 reveals that while the hourly concentrations of CO, SO2 and NO2 were mostly within the National Ambient Air Quality Standards (NAAQs) of Thailand, the hourly concentrations of O3 frequently exceeded the standard. The results reveal that the problem of high O3 concentration continuously persisted in this area. The O3 photolytic rate constant (j1) for BMR calculated based on assuming a phot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Daily activity cycles, and speciation of NMVOC emissions (see Supplementary Information, Table S1), have been imposed (see details in Chen et al 43 and Lowe). 44 The 25 study are caused by the fact that the Bangkok data set is a much longer data set, and the initial years of the study (2005)(2006)(2007)(2008)(2009) resulted in much higher local pollution levels as emissions control technologies or vehicle fleet composition were not implemented during this time period. Fig.…”
Section: Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily activity cycles, and speciation of NMVOC emissions (see Supplementary Information, Table S1), have been imposed (see details in Chen et al 43 and Lowe). 44 The 25 study are caused by the fact that the Bangkok data set is a much longer data set, and the initial years of the study (2005)(2006)(2007)(2008)(2009) resulted in much higher local pollution levels as emissions control technologies or vehicle fleet composition were not implemented during this time period. Fig.…”
Section: Modellingmentioning
confidence: 99%
“…This might be explained by the mobile sources (e.g. vehicles) in Bangkok Metropolitan Region, 25 which is highly dependent on traffic density and traffic flow. The NO x emissions from vehicles are dependent on fuel type and speed of the vehicles, 50 which can be responsible for the variation of the [OX] L for different roadside sites in Bangkok.…”
Section: Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In additional, many studies report that O3 concentrations had increasing trends [28][29][30], while in this study we found decreasing O3 concentrations over Greater Bangkok. NO2 is an oxidation product from Nitrogen oxides (NOx) and O3, which is emitted from combustion sources such as vehicle exhausts, industries, power plants and residential heating [14]. Thus, this decrease in O3 could be due to greater increases in NO2 concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bangkok has experienced winter pollution events with more frequency. Previous studies have mentioned that the common sources of PM2.5 emissions in Bangkok are from biomass burning, traffic and industrial activities with varying concentration caused by seasonal factors [12][13][14]. Moreover, Watcharavitoon, et al [15] presented spatial and temporal variation trends of gaseous air pollutant concentrations for O3, NOx, CO, and SO2 from 1996 to 2009 in Bangkok between residential and roadside areas.…”
Section: Introductionmentioning
confidence: 99%